2009
DOI: 10.1577/t06-243.1
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Vulnerability to Angling in Largemouth Bass

Abstract: Abstract.-Although a great deal of effort has been expended to try to understand the consequences of fishing-induced selection by commercial fisheries, relatively little effort has been put into trying to understand the selective effects of recreational angling. We conducted a long-term selection experiment to assess the heritability of vulnerability to angling in largemouth bass Micropterus salmoides. Three successive generations of artificially selected largemouth bass were produced from a single experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
266
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(278 citation statements)
references
References 49 publications
12
266
0
Order By: Relevance
“…That is, negative effects of this fisheries-induced evolution on population-level recruitment in the wild would be expected to be strongest in environments with abundant food resources (i.e., where LV are benefiting less from their lower metabolic rate), with short spawning seasons (i.e., where the opportunity to respawn after brood loss is limited, e.g., in northern latitudes), and with overall high egg predation potential (i.e., where the added wariness/timidity of LV-like fish would result in a greater reduction in fitness due to increased brood predation). In addition, fisheries-induced evolution to LVlike genotypes would almost certainly be accompanied by a concomitant decline in catchability on a population-level scale (18), a scenario that would be undesirable for recreational anglers that value catch rates (38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, negative effects of this fisheries-induced evolution on population-level recruitment in the wild would be expected to be strongest in environments with abundant food resources (i.e., where LV are benefiting less from their lower metabolic rate), with short spawning seasons (i.e., where the opportunity to respawn after brood loss is limited, e.g., in northern latitudes), and with overall high egg predation potential (i.e., where the added wariness/timidity of LV-like fish would result in a greater reduction in fitness due to increased brood predation). In addition, fisheries-induced evolution to LVlike genotypes would almost certainly be accompanied by a concomitant decline in catchability on a population-level scale (18), a scenario that would be undesirable for recreational anglers that value catch rates (38).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a trait that renders individuals more vulnerable to capture likely also varies across different taxa and/or fisheries. In some fisheries, such as recreational angling, selection seems to operate on angling vulnerability as a complex, heritable trait composed of a range of covarying physiological, behavioral, and life history traits (17,18), rather than body size per se. In the popular recreational fish species largemouth bass (Micropterus salmoides), for example, it has been shown that fish with higher vulnerability to angling also exhibit higher metabolic rates and more intensive parental care (19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional work is needed to examine the extent to which group size may be altered via under direct or indirect selection on sociability by trap fisheries, potentially generating an evolutionary shift toward less social fish. The present study contributes to the growing body of evidence suggesting that both behavior and physiology are important aspects FIE (Alós et al., 2016; Biro & Sampson, 2015; Philipp et al., 2009). More information is still needed to answer whether, and to what level, the harvest of fish in the wild can lead to persistent behavioral and physiological change over generations.…”
Section: Discussionmentioning
confidence: 99%
“…Biro and Stamps (35) argued that behaviors such as boldness and activity, which are often correlated with growth rate, are likely to affect productivity and could respond to selective mortality. Philipp et al (36) reported differences in hook-and-line angling vulnerability between individual largemouth bass (Micropterus salmoides) in a wild population. The authors estimated a realized heritability of 0.15 through a 3-generation selection experiment.…”
Section: Fishingmentioning
confidence: 99%